Rethinking God as gift : Marion, Derrida, and the limits of phenomenology - Horner, Robyn (Perspectives in continental philosophy, 2001)
Rethinking God as Gift is situated at the intersection of philosophy, critical theory and theology. The first sustained study of the work of Jean-Luc Marion in English, it offers a unique perspective on contemporary questions and their theological relevance. Taking its point of departure from the problem of the gift as articulated by Jacques Derrida, who argues that the conditions of possibility of the gift are also its conditions of impossibility, Horner pursues a series of questions concerning the nature of thought, the viability of phenomenology, and, most urgently, the possibility of grace.